Platinum-Based Chemotherapy and Immunotherapy in Early Triple-Negative Breast Cancer: A Meta-Analysis and Indirect Treatment Comparison - He, Qin; Peng, Yicheng; Sun, Jie; Liu, Jianxia (Frontiers in Oncology, 2021)
Background: Triple-negative breast cancer(TNBC) comprises 15% of invasive breast cancers. Platinum-based chemotherapy and immune checkpoint inhibitors(ICIs) have been extensively researched in recent years as promising treatments in the neoadjuvant setting. However, clinical data is lacking in direct comparisons of these two treating regimens. Methods: We conducted an online search on PubMed, Embase, Cochrane Online Library and key oncological meetings for available randomized controlled trials(RCTs) investigating ICIs or platinum drugs versus anthracyclines and taxane-based neoadjuvant chemotherapy (AT-based NACT). The conventional meta-analyses were conducted separately, then indirect comparisons for clinical efficacy and safety profile were performed between ICIs and platinum drugs using AT-based NACT as a common comparator. Results: Seven random controlled trials (RCTs) with 1647 patients were included in the meta-analysis. The indirect comparison demonstrated that ICIs plus chemotherapy significantly improved pathological complete response (pCR) rate (p=0.00445, OR, 1.78; 95%CI, 0.70-4.53), and decreased the adverse effect(AE) related discontinuance versus platinum-based chemotherapy (P=0.00015; OR 0.46; 95%CI, 0.26-0.82). Conclusion: ICIs plus chemotherapy showed increased pCR rate and decreased adverse effects compared with platinum-based chemotherapy in early TNBC. However, subgroup analysis and survival data to explore the proper patients for each treatment remains scarce. Therefore, further studies with powered direct comparisons of these two treating regimens are required.